Penghapusan Pertanggungjawaban Pidana Terhadap Pengemudi Dalam Kecelakaan Lalu Lintas (Studi Implementasi Undang-Undang No. 22 Tahun 2009 Tentang Lalu Lintas dan Angkutan Jalan di Polres Sragen) - Virdananjaya, Diaz; , Dr. Natangsa Surbakti, S.H., M.Hum; , Marisa Kurnianingsih, S.H., M.H., M.Kn (2016)
Traffic accidents in Indonesia each year has proven to cause various damages to the parties, especially the driver. Handling traffic accidents it self is regulated by Law Number 22 Year 2009 regarding Traffic and Road Transportation. Can not be denied also that there was some kind of accident that could stop the legal process because it does not meet the elements of a criminal offense. Prove it to do so in the juridical empirical research in order to synchronize the Act with the fact that field. Among the many areas in Indonesia, Sragen in this case has a number of times to apply the termination of the investigation against the driver because there is an element that is capable of removing criminal liability for the driver, characterized by the issuance of Warrant Termination of Investigation. As for the legal process stops at the stage of investigation, either through examination of fast events, short, and plain.